Differential expression of alternatively spliced transcripts related to energy metabolism in colorectal cancer. (December 2016) - Snezhkina, Anastasiya; Krasnov, George; Zaretsky, Andrew; Zhavoronkov, Alex; Nyushko, Kirill; Moskalev, Alexey; Karpova, Irina; Afremova, Anastasiya; Lipatova, Anastasiya; Kochetkov, Dmitriy; Fedorova, Maria; Volchenko, Nadezhda; et al.
Abstract Background Colorectal cancer (CRC) is one of the most common malignant tumors worldwide. CRC molecular pathogenesis is heterogeneous and may be followed by mutations in oncogenes and tumor suppressor genes, chromosomal and microsatellite instability, alternative splicing alterations, hypermethylation of CpG islands, oxidative stress, impairment of different signaling pathways and energy metabolism. In the present work, we have studied the alterations of alternative splicing patterns of genes related to energy metabolism in CRC. Results Using CrossHub software, we analyzed The Cancer Genome Atlas (TCGA) RNA-Seq datasets derived from colon tumor and matched normal tissues. The expression of 1014 alternative mRNA isoforms involved in cell energy metabolism was examined. We found 7 genes with differentially expressed alternative transcripts whereas overall expression of these genes was not significantly altered in CRC. A set of 8 differentially expressed transcripts of interest has been validated by qPCR. These eight isoforms encoded byOGDH, COL6A3, ICAM1, PHPT1, PPP2R5D, SLC29A1, andTRIB3 genes were up-regulated in colorectal tumors, and this is in concordance with the bioinformatics data. The alternative transcript NM_057167 ofCOL6A3 was also strongly up-regulated in breast, lung, prostate, and kidney tumors. Alternative transcript ofSLC29A1 (NM_001078177) was up-regulated only in CRC samples, but not in the other tested tumor types. Conclusions We identified tumor-specific expression of alternative spliced transcripts of seven genes involved in energy metabolism in CRC. Our results bring new knowledge on alternative splicing in colorectal cancer and suggest a set of mRNA isoforms that could be used for cancer diagnosis and development of treatment methods.